(untitled) (KULT_online, 2011)
For the series of "Blackwell Companions to Literature and Culture", editors Charles J. Rzepka and Lee Horsley offer A Companion to Crime Fiction (2010), an essay collection aimed at undergraduate and graduate students. The 47 contributions to the volume focus on the British-American genres of detective and crime fiction and are written by literary and film critics as well as practitioners in the fields. Covering the period from the origins of crime fiction in the eighteenth century up to the present day, the detailed essays in the Companion are based on a variety of theoretical approaches and methodologies ranging from formal criticism to race, class, and gender studies as well as more encyclopaedic approaches. Despite a few terminological shortcomings, such as the inconsistent narratological distinction between detective and crime fiction, the volume constitutes a recommendable introduction, which might also help to further the scholarly discussion of the genre.